QUANTITATIVE BIOIMAGING an introduction to biology, instrumentation, experiments, and data... analysis for scientists and engineers. - Ober, Raimund J.; Ward, E. Sally; Chao, Jerry ([S.l.] : CRC PRESS, 2020)
Quantitative bioimaging is a broad interdisciplinary field that exploits tools from biology, chemistry, optics, and statistical data analysis for the design and implementation of investigations of biological processes. Instead of adopting the traditional approach of focusing on just one of the component disciplines, this textbook provides a unique introduction to quantitative bioimaging that presents all of the disciplines in an integrated manner. The wide range of topics covered include basic concepts in molecular and cellular biology, relevant aspects of antibody technology, instrumentation and experimental design in fluorescence microscopy, introductory geometrical optics and diffraction theory, and parameter estimation and information theory for the analysis of stochastic data. Key Features: Comprises four parts, the first of which provides an overview of the topics that are developed from fundamental principles to more advanced levels in the other parts. Presents in the second part an in-depth introduction to the relevant background in molecular and cellular biology and in physical chemistry, which should be particularly useful for students without a formal background in these subjects. Provides in the third part a detailed treatment of microscopy techniques and optics, again starting from basic principles. Introduces in the fourth part modern statistical approaches to the determination of parameters of interest from microscopy data, in particular data generated by single molecule microscopy experiments. Uses two topics related to protein trafficking (transferrin trafficking and FcRn-mediated antibody trafficking) throughout the text to motivate and illustrate microscopy techniques. An online appendix providing the background and derivations for various mathematical results presented or used in the text is available at http://www.routledge.com/9781138598980.
OCLC-licensed vendor bibliographic record.
Keywords: Imaging systems in biology; Bioinformatics; Computational biology; MEDICAL / Biotechnology; SCIENCE / Microscopes & Microscopy; SCIENCE / Physics